Outcome effectiveness of the lay health advisor model among Latinos in the United States: an examination by role - Ayala, Guadalupe X. (Oxford University Press, 2010)
The objective of this study was to examine lay health advisor (LHA) programs designed to promote health among US Latinos and the extent to which educator-only versus educator-plus-bridge programs differed in designs and outcomes achieved. Two independent coders reviewed 128 published articles on LHAs yielding information at two levels: (i) study design and participant and LHA characteristics from 61 studies that broadly compared educator-only versus educator-plus-bridge programs and (ii) implementation features and outcomes from 17 randomized controlled trials or quasi-experimental studies with outcome data. LHA programs have been widely used with Latinos in certain US regions; our findings indicate that LHAs are effective intervention agents. We identified differences between educator-only and educator-plus-bridge LHA programs, although the small number of educator-plus-bridge programs with outcome data limited comparisons. Major gaps remain in research targeting Latino subgroups other than Mexican immigrants/Mexican Americans. Sufficient research has evaluated LHA programs among Latinos on their ability to achieve health behavior and/or health status changes. In the future, more of a focus on organizational and policy changes is warranted. Questions remain about diversity in LHAs’ characteristics and roles, which influence not only outcomes but also program sustainability and dissemination.